2000
DOI: 10.1002/1522-7278(2000)15:5<513::aid-tox22>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimutagenic and desmutagenic effects of humic and fulvic acids on root tips ofVicia faba

Abstract: Humic acids HA and fulvic acids FA of different origin were evaluated for their antimutagenic and/ or desmutagenic activity on Vicia faba germinating seeds treated with the mutagen ( ) compound maleic hydrazide MH . Both HA and FA were tested at two different concentrations, 20 and 200 mg L y1 , either alone or together with 10 mg L y1 of MH. Two experimental procedures were used to investigate the occurrence and nature of the antimutagenic or desmutagenic activity. In procedure 1, HA or FA and MH were interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
(23 reference statements)
4
13
0
Order By: Relevance
“…Our results have shown that dicamba caused DNA hypomethylation. In recent years, several studies have been published indicating the protective effect of HAs against toxic element such as cadmium, zinc, mitomycin C, mercury and maleic hydrazide mercury in different animals and plants (De Marco et al 1999;Ferrara et al 2000Ferrara et al , 2006Hammock et al 2003;Koukal et al 2003;Voets et al 2004). The protective effects of HAs have been reported to be primarily associated with its presence in glutathione (GSH) biosynthesis, which are known to protect DNA and other cellular components from damage by oxygen radicals (Vaughan et al 1985;Concheri et al 1994;De Marco et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results have shown that dicamba caused DNA hypomethylation. In recent years, several studies have been published indicating the protective effect of HAs against toxic element such as cadmium, zinc, mitomycin C, mercury and maleic hydrazide mercury in different animals and plants (De Marco et al 1999;Ferrara et al 2000Ferrara et al , 2006Hammock et al 2003;Koukal et al 2003;Voets et al 2004). The protective effects of HAs have been reported to be primarily associated with its presence in glutathione (GSH) biosynthesis, which are known to protect DNA and other cellular components from damage by oxygen radicals (Vaughan et al 1985;Concheri et al 1994;De Marco et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Antimutagenic activity of soil humic extracts was studied mostly in Vicia faba test (Ferrara et al 2000(Ferrara et al , 2004. In addition HAs have shown to cause decreasing number of genetic anormalies in seedlings of Vicia faba, treated with various herbicides Ferrara et al 2000Ferrara et al , 2004. Ferrara et al (2004) have described that the anticlastogenic activity of HAs is a particular aspect of the general antimutagenic action and refers specifically to the reduction of chromosome breakages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biological and physicochemical properties of ions are changed dramatically as a result of complexation with humin substances [Senesi and Loffredo, 1999]. The adsorbing capacity of humic and fulvic acids for poisons and mutagen molecules may be a reason for the antitoxic and desmutagenic effects of these acids [Sato et al, 1987;Badaev et al, 1989;Ferrara et al, 2000].…”
Section: Characteristics and Pharmacological Properties Of Fulvic Andmentioning
confidence: 99%